Risk and Reflection in the Academic Workplace. Issue 3 (August 2020) - Walker, Judith; Oldford, Stephanie
The Problem: Universities are workplaces designed for learning, research, and reflection. In recent years, an amalgam of issues, both internal and external, have emerged, making critical reflection more difficult and riskier for both academic and nonacademic staff. The Solution: We argue that positive leadership, dialogue, and group connection can help counter increasing isolation and in effect make reflection more possible. The Stakeholders: This article is relevant not only to human resource development (HRD) scholars and practitioners within the context of postsecondary institutions but also to large and complex bureaucratic organizations grappling with a changing landscape of employment.